III Conferencia por la Paz y la Soberanía en Centroamérica México y el Caribe
Poster for a conference held in April 1982 in San José, Costa Rica. Stylised dove holding an olive branch which’s leaves are the flags of different central American and Caribbean countries. Suggested translation: III Conference for Peace and Sovereignty in Central America Mexico and the Caribbean. PO-2216